Use of autologous adipose‐derived mesenchymal stem cells for creation of laryngeal cartilage. (14th December 2017) - Zhang, Hongji; Voytik‐Harbin, Sherry; Brookes, Sarah; Zhang, Lujuan; Wallace, Joseph; Parker, Noah; Halum, Stacey
Abstract : Objectives/Hypothesis: Adipose‐derived mesenchymal stem cells (ASCs) are an exciting potential cell source for tissue engineering because cells can be derived from the simple excision of autologous fat. This study introduces a novel approach for tissue‐engineering cartilage from ASCs and a customized collagen oligomer solution, and demonstrates that the resultant cartilage can be used for laryngeal cartilage reconstruction in an animal model. Study Design: Basic science experimental design. Methods: ASCs were isolated from F344 rats, seeded in a customized collagen matrix, and cultured in chondrogenic differentiation medium for 1, 2, and 4 weeks until demonstrating cartilage‐like characteristics in vitro. Large laryngeal cartilage defects were created in the F344 rat model, with the engineered cartilage used to replace the cartilage defects, and the rats followed for 1 to 3 months. Staining examined cellular morphology and cartilage‐specific features. Results: In vitro histological staining revealed rounded chondrocyte‐appearing cells evenly residing throughout the customized collagen scaffold, with positive staining for cartilage‐specific markers. The cartilage was used to successfully repair large cartilaginous defects in the rat model, with excellent functional results. Conclusions: This study is the first study to demonstrate, in an animal model, that ASCs cultured in a unique form of collagen oligomer can create functional cartilage‐like grafts that can be successfully used for partial laryngeal cartilage replacement. Level of Evidence: NA. Laryngoscope, 128:E123–E129, 2018